Problems of (Un)translatability in the Yakut Epic Text Olonkho - Nakhodkina, Alina A.; Находкина, А.А. (Сибирский федеральный университет. Siberian Federal University., 2013)
The author revisits the issues of untranslatability in the context of cross-cultural communication and analyzed translation as a means of cross-cultural contact. The nature of the problem of (un) translatability is discussed from Wilhelm von Humboldt’s view of language as “an expression of the spirit of a nation” and from the perspective of the linguistic relativity hypothesis which views language as “a mediator of thought”. The research as part of a large translation project is based on the material of the Olonkho – a Yakut (Sakha) heroic epic poem. The analysis of various linguistic and cultural barriers including lexical gaps as main stumbling blocks while translating is given as well as a brief description of Olonkho Автор исследует проблему (не)переводимости в контексте кросс-культурной коммуникации и перевода как средства межкультурного контакта. Проблема (не)переводимости рассматривается с точки зрения Вильгельма фон Гумбольдта, который считал язык «выражением духа нации», и гипотезы лингвистической относительности, которая определяет язык как «медиатор мысли». Настоящее исследование является частью крупного проекта по переводу олонхо – якутского (саха) героического эпоса «Нюргун Боотур Стремительный» П.А. Ойунского. В статье проводится анализ различных языковых и культурных барьеров, дается краткое описание олонхо